1987
DOI: 10.3758/bf03210507
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific serial position effects in comparisons of multiletter strings

Abstract: Several recent studies of multiletter matching have included pairs in which the two letter strings have the same letters but in different orders. The latency of responses and the error rates to these rearranged pairs vary as a function of the total number of positions by which the letters in one string are displaced in the other. When order is relevant, and the rearranged pairs are classified as "different" (the order task), both response measures decrease as displacement increases. Similar, but mirror-image, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Proctor and Healy (1987) presented evidence that could have suggested that, in a same-different matching task, an observer's processing strategy changes depending on the task demands. When observers were required to respond "same" only when the items in the two arrays were physically the same and in the same positions (the order-relevant task), position effects were different from those observed when the position of the stimulus items was irrelevant (the orderirrelevant task).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Proctor and Healy (1987) presented evidence that could have suggested that, in a same-different matching task, an observer's processing strategy changes depending on the task demands. When observers were required to respond "same" only when the items in the two arrays were physically the same and in the same positions (the order-relevant task), position effects were different from those observed when the position of the stimulus items was irrelevant (the orderirrelevant task).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, the difference in response frequency creates o problem for interpreting the results. By factorially manipulat109task and response frequency, Proctor and Healy (1987) showed that response frequency does not influence the patterns of permutation and replacement effects that are obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The order task shows an exaggerated left-to-right serialposition effect relative to the item task when replacement letters are equally likely in all positions (Proctor & Healy, 1987). It is well known that presentation probabilities systematically affect RTs in visual search and detection (see, e.g., Shaw, 1982;Theios, Smith, Haviland, Traupmann, & Moy, 1973).…”
Section: Experiments 1 Andmentioning
confidence: 99%
See 2 more Smart Citations